A Case Of Communited Proximal Humerus Fracture With Osteoporotic Degeneration Treated By Reverse Shoulder Arthroplasty (Journal of Pharmaceutical Negative Results, 2023)
Following a ground-level fall on an extended arm, proximal humerus fractures are typical fractures often found in elderly individuals with osteoporotic bone.1,2 Managing fractures in the proximal part of humerus might be difficult if the fracture associated with it is complex.3 While many patients benefit from surgery, others, particularly older individuals with valgus affected proximal humerus fractures, are effectively handled non-surgically. Age-related complicated fractures in the proximal part of humerus which might be 3 part or 4 parts are increasingly being treated with reverse shoulder arthroplasty.4,5,6 76 yr Old aged postmenopausal women allegedly fall down from her bike and was brought to our hospital. A fractured proximal humerus was discovered on radiology.8 The indications for the usage of new technique reverse shoulder arthroplasty have been in the increasing trends over few decades which include deficiency at the rotator cuff muscle, major nonrecoverable tears at the rotator cuff muscles, fractures less than 3 weeks, native treatment which may lead to recurrent dislocations, non-union and most common complication malunion and for revision arthroplasty, and for any lifesaving salvage conditions.7,8,9 The patient had reverse shoulder arthroplasty, and all of his or her functions were fully recovered. The majority of patients report pain reduction and better function, and patient satisfaction with RTSA may be high.10,11,12 The long-term effects remain unclear, despite the fact that the implant survival rate seems to be satisfactory in the short term. Contrary to expectations, Reverse Shoulder Arthroplasty is linked to a greater rate and wider range of problems. To make this therapy as effective as possible for numerous shoulder disorders, improvements in prosthesis design, surgeon expertise, and clinical outcomes are required.13,14